Plants mentioned in the Islamic Scriptures (HolyQur'ân and Ahadith): traditional uses and medicinal importance in contemporary times - El-Seedi, Hesham Rushdey; Khalifa, Shaden Ali M.; Yosri, Nermeen; Khatib, Alfi; Chen, Lei; Saeed, Aamer; Efferth, Thomas; Verpoorte, Robert (Elsevier Ireland Ltd, 2019)
Ethnopharmacological relevance: Over the past thousand years, Islamic physicians have collected cultural, philosophical, sociological and historical backgrounds for understanding diseases and medications. The Prophet Mohammed (Peace Be Upon Him (PBUH) said: “There is no disease that Allah has created, except that Allah also has created its cure.” Therefore, Islamic scholars are encouraged to explore and use both traditional and modern forms of medicine. Aim of the study: (1) To identify some of the medicinal plants mentioned in the Holy Qur'ân and Ahadith textbooks of the period 700–1500 AD; (2) to compare them with presently used traditional medicines; (3) to evaluate their value based on modern research; and (4) to investigate the contributions of Islamic scholars to the development of the scientific branches, particularly medicine. Materials and methods: A literature search was performed relating to 12 medicinal plants mentioned in the Holy Qur'ân and Ahadith using textbooks, Al-Azhar scholars, published articles, the plant list website (http://www.theplantlist.org/), the medicinal plant names services website (http://mpns.kew.org/mpns-portal/) and web databases (PubMed, Science Direct, and Google Scholar). Results and discussion: The Islamic Golden Age was a step towards modern medicine, with unique insights and multi-disciplinary aspects. Traditional Islamic Medicine has had a significant impact on the development of various medical, scientific and educational activities. Innumerable Muslim and non-Muslim physicians have built on the strong foundation of Traditional Islamic Medicine by translating the described natural remedies and effects. The influences of different ancient cultures on the traditional uses of natural products were also documented in Islamic Scriptures in the last part of the second millennium. The divine teachings of Islam combine natural and practical healing and incorporate inherited science and technology. Conclusion: In this review, we discuss Traditional Islamic Medicine with reference to both medical recommendations mentioned in the Holy Qur'ân and Prophetic Traditional Medicine (al-Tibb al-Nabawi). Although the molecular mechanisms and functions of some of the listed medicinal plants and their derivatives have been intensively studied, some traditional remedies have yet to be translated into clinical applications.